Wheat leaf rust fungus effector Pt13024 is avirulent to TcLr30 - Qi, Yue; Li, Jianyuan; Mapuranga, Johannes; Zhang, Na; Chang, Jiaying; Shen, Qianhua; Zhang, Yue; Wei, Jie; Cui, Liping; Liu, Daqun; Yang, Wenxiang (Frontiers in Plant Science, 2023)
Wheat leaf rust, caused by Puccinia triticina Eriks. (Pt), is a global wheat disease threatening wheat production. Dissecting how Pt effector proteins interact with wheat has great significance in understanding the pathogenicity mechanisms of Pt. In the study, the cDNA of Pt 13-5-72 interacting with susceptible cultivar Thatcher was used as template to amplify Pt13024 gene. The expression pattern and structure of Pt13024 were analyzed by qRT-PCR and online softwares. The secretion function of Pt13024 signal peptide was verified by the yeast system. Subcellular localization of Pt13024 was analyzed using transient expression on Nicotiana benthamiana. The verification that Pt13024 inhibited programmed cell death (PCD) was conducted on N. benthamiana and wheat. The deletion mutation of Pt13024 was used to identify the virulence function motif. The transient transformation of wheat mediated by the type III secretion system (TTSS) was used to analyze the activity of regulating the host defense response of Pt13024. Pt13024 gene silencing was performed by host-induced gene silencing (HIGS). The results showed that Pt13024 was identified as an effector and localized in the cytoplasm and nucleus on the N. benthamiana. It can inhibit PCD induced by the Bcl-2-associated X protein (BAX) from mice and infestans 1 (INF1) from Phytophthora infestans on N. benthamiana, and it can also inhibit PCD induced by DC3000 on wheat. The amino acids 22 to 41 at N-terminal of the Pt13024 are essential for the inhibition of programmed cell death (PCD) induced by BAX. The accumulation of reactive oxygen species and deposition of callose in near-isogenic line TcLr30, which is in Thatcher background with Lr30, induced by Pt13024 was higher than that in 41 wheat leaf rust-resistant near-isogenic lines (monogenic lines) with different resistance genes and Thatcher. Silencing of Pt13024 reduced the leaf rust resistance of Lr30 during the interaction between Pt and TcLr30. We can conclude that Pt13024 is avirulent to TcLr30 when Pt interacts with TcLr30. These findings lay the foundation for further investigations into the role of Pt effector proteins in pathogenesis and their regulatory mechanisms.